2006
DOI: 10.1038/sj.onc.1209281
|View full text |Cite
|
Sign up to set email alerts
|

Loss of SOCS3 in the liver promotes fibrosis by enhancing STAT3-mediated TGF-β1 production

Abstract: Recently, DNA methylation and reduced expression of the suppressor of the cytokine signaling-3 (SOCS3) gene in human hepatocellular carcinoma (HCC) patients have been reported. However, the roles of SOCS3 in HCC development in vivo have not been clarified. Using RT-PCR analysis and Western blotting, we confirmed that SOCS3 expression was reduced in HCC patients. However, reduced expression of SOCS3 occurred not only in HCC but also in nontumor regions, and this reduction was stronger as the fibrosis grade incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
206
1
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(221 citation statements)
references
References 42 publications
(60 reference statements)
13
206
1
1
Order By: Relevance
“…Phenotypic effects of IEC-SOCS3 deletion on colon tumorigenesis were associated with enhanced activation of STAT3, NF-kB and STAT1, indicating that during chronic inflammation, SOCS3 normally limits activation of multiple signaling pathways implicated in risk of CAC. Effects of SOCS3 deletion on STAT3 activation are consistent with data in other cell types, suggesting that the major role of SOCS3 is to limit hyperactivation of STAT3 by proinflammatory cytokines, particularly IL-6 (Croker et al, 2003;Ogata et al, 2006a). Findings that SOCS3 effectively inhibits STAT3 activation by IL-6 trans-signaling, as well as by IL-6 alone is relevant to evidence for a major role of IL-6 trans-signaling in CAC (Becker et al, 2004).…”
Section: Discussionsupporting
confidence: 75%
“…Phenotypic effects of IEC-SOCS3 deletion on colon tumorigenesis were associated with enhanced activation of STAT3, NF-kB and STAT1, indicating that during chronic inflammation, SOCS3 normally limits activation of multiple signaling pathways implicated in risk of CAC. Effects of SOCS3 deletion on STAT3 activation are consistent with data in other cell types, suggesting that the major role of SOCS3 is to limit hyperactivation of STAT3 by proinflammatory cytokines, particularly IL-6 (Croker et al, 2003;Ogata et al, 2006a). Findings that SOCS3 effectively inhibits STAT3 activation by IL-6 trans-signaling, as well as by IL-6 alone is relevant to evidence for a major role of IL-6 trans-signaling in CAC (Becker et al, 2004).…”
Section: Discussionsupporting
confidence: 75%
“…28,29 It has been also proposed that IL-10 is able to inhibit HSC activation and to promote their apoptosis during liver fibrogenesis. 28,29 Beside its well-known interference with the pro-inflammatory cytokine signaling pathways, 30,31 SOCS3 has been found to negatively regulate fibrogenesis in the liver 32,33 and to suppress the signaling molecule STAT3, which activates TGF-b transcription. 32 Our data demonstrate that the hepatic expression of all these molecules are deeply affected in cirrhosis leading to a pro-fibrogenic environment, which is fully counteracted by CB1 receptor antagonism.…”
Section: Endocannabinoids and Liver Cirrhosismentioning
confidence: 99%
“…It was reported that STAT3 positively regulates TGF-b1 promoter activity and enhances TGF-b1 production (14,15). Intracellular staining revealed significantly enhanced STAT3 phosphorylation in the Egr-3-transduced CD4 + cells compared with the GFPnegative cells (Fig.…”
Section: Egr-3 Enhances the Phosphorylation Of Stat3mentioning
confidence: 96%
“…Th3 cells (12) and CD4 + CD25 2 latency-associated peptide (LAP) + T cells (13) are reported to secrete TGF-b1; however, the regulation of TGF-b1 secretion is not fully understood. It was reported that STAT3 positively regulates TGF-b1 promoter activity and enhances TGF-b1 production (14,15). Han et al (16) reported that the binding of CD69 maintains the expression of membranebound TGF-b1 on CD4 + CD25 2 CD69 + T cells via ERK activa-tion.…”
mentioning
confidence: 99%